Los Nombres Científicos - Jorge R. Rey (EDIS)
ENY-731S, a 5-page illustrated fact sheet by Jorge Rey, a Spanish Language version of ENY-731: Scientific Nomenclature: What's in a Name? It explores the practice of using scientific names for plants and animals. He discusses why we need scientific names, the history of scientific nomenclature, "grammar" and what the different parts of a scientific name mean. Includes links to additional references. Published by the UF Department of Entomology and Nematology, June 2006.